Economia política de petróleo e gás: A experiência russa - Giorgio Romano Schutte (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– The recovery of Russia`s center of power through a national development strategy during the Putin administration was the basis for revising the state`s energy-sector policy. The government drastically increased the role of the state in the energy sector, raising state control over the sector`s assets to as much as 47% in late 2007, up from less than 10% in 2000, when Putin took office. The core objective, however, was never to purge the private sector from this business, but rather to regain state control over strategic sectors. The policy of keeping majority control in national hands is part of a context involving a development strategy and also an industrial policy aimed at creating national champions. This policy of partial re-nationalization also implied new standards in relations with foreign companies. From August 1998 to September 2008, Russia`s real GDP doubled in size. Economic growth was accompanied by gains in productivity and real wages, as well as lower unemployment and poverty levels. Even so, Russia was one of the countries hardest hit by the global financial crisis, thus revealing two outstanding problems: first of all, the pre-eminence of extractive activities and, second, the under-developed national financial system, which provoked a high degree of dependence on the entry of short-term capital. Both factors raise the challenge of modernization and innovation for the Russian economy, and will require the development of mechanisms to promote a greater spread effect from energy to other sectors of the economy.
Keywords: L71; O13; Q38; 330